Serum Ferritin Levels in Pregnancy and Their Association with Gestational Diabetes Mellitus: A Prospective Longitudinal Study - Qin Z; Du Y; Wang Z; Qin X; Wu H; Yu X; Zhao C; Mo L; Huang B (Diabetes, Metabolic Syndrome and Obesity)
Zhenhua Qin,1 Yao Du,1 Zidi Wang,1 Xianfeng Qin,1 Hongchi Wu,1 Xiangyuan Yu,1 Chaochao Zhao,1 Lei Mo,2 Bo Huang1 1Guangxi Key Laboratory of Diabetic Systems Medicine, Guangxi Key Laboratory of Environmental Exposomics and Life-Course Health, Guangxi Health Commission Key Laboratory of Health and Care for Life-Course, School of Public Health, Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 2Department of Obstetrics and Gynecology, the Second Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of ChinaCorrespondence: Bo Huang, Guangxi Key Laboratory of Diabetic Systems Medicine, Guangxi Key Laboratory of Environmental Exposomics and Life-Course Health, Guangxi Health Commission Key Laboratory of Health and Care for Life-Course, School of Public Health, Guilin Medical University, Guilin, Guangxi, 541199, People’s Republic of China, Tel +86-773-5591452, Email Bo.Huang@glmc.edu.cn Lei Mo, Department of Obstetrics and Gynecology, the Second Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, 541199, People’s Republic of China, Email 50442117@qq.comObjective: Elevated serum ferritin (SF) levels are associated with oxidative stress (OS) and systemic inflammation in various disorders. However, the changes in SF levels during pregnancy and their relationship with gestational diabetes mellitus (GDM) and blood glucose levels are not well understood.Methods: This prospective longitudinal study included 390 participants (130 GDM cases and 260 controls) during early pregnancy. We measured SF levels in the1st, 2nd, and 3rd trimesters, as well as plasma malondialdehyde (MDA) and C-reactive protein (CRP) in the 1st trimester, blood glucose levels in the oral glucose tolerance test (OGTT), and glycosylated hemoglobin (HbA1c) in the 2nd trimester. We used Spearman’s rank correlation to estimate the association between SF, OS, inflammation and glucose levels. Logistic regression analysis was performed to estimate the OR of GDM associated with SF. Multiple stepwise regression models were used to assess the relationship between glucose levels and the risk factors.Results: SF levels decreased with increasing gestation in the study population. Compared to controls, GDM patients had significantly higher levels of SF (1st and 2nd trimesters), MDA, CRP, and HbA1c. SF was positively correlated with MDA and fasting plasma glucose (FPG). Elevated SF levels during early pregnancy were significantly associated with increased GDM risks (OR = 2.024, 95% CI: 1.076 – 3.807). The explanatory variables that contributed to increased glucose levels were SF, MDA, body mass index (BMI), maternal age, and family history of diabetes.Conclusion: SF is significantly associated with GDM and may be a potential biomarker for GDM in early pregnancy.Keywords: gestational diabetes mellitus, ferritin, oxidative stress, inflammation